If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 12 = 27 Reorder the terms: 12 + 8x = 27 Solving 12 + 8x = 27 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 8x = 27 + -12 Combine like terms: 12 + -12 = 0 0 + 8x = 27 + -12 8x = 27 + -12 Combine like terms: 27 + -12 = 15 8x = 15 Divide each side by '8'. x = 1.875 Simplifying x = 1.875
| y-5=3(x-6) | | 9x+y=72 | | (11x)-5=180 | | x/3=5+x-5/5 | | x/9=3x/7-20 | | 1+2=? | | 1+2=8 | | 2. 3/2y-d4=5/3(y+4)-2/3 | | x^2-5=-4x^2-3x | | 36x-100-4(x^2)=0 | | x/2-1=x/5+1 | | 9p-6q=20 | | 2x=73-3 | | 5y+2y+12=4y-4-2 | | 16x^2-8x+1=-x^2+5 | | 7+3x=22-10x | | H-17=17 | | 3/2y-4=5/3(y+4)-2/3 | | 3(xX-5)=21 | | 24-n=7 | | 7+3x=2[11-5X] | | A+37=42 | | -3x+9y=57 | | 5x-y=54 | | 18-3x=13+2x | | 2x-8+31=180 | | 17x+9/2-16x=1/8 | | x+15/7=-2/7 | | 9(x+2)-3=3x+6(3+x) | | 4(x+2)-8=2x+2(-2+x) | | 4(x+2)-8=2x+(-2+x) | | 6x+3=-3+14 |